Pengaruh Pendidikan Kesehatan dengan Media Leaflet terhadap Pengetahuan Remaja Putri dalam Deteksi Dini Kanker Payudara Melalui Pemeriksaan Payudara Sendiri (Sadari) Di SMA.N 8 Kota Jambi - Efni, Nel; Fatmawati, Tina Yuli (Jurnal Ilmiah Universitas Batanghari Jambi, 2021)
The prevalence of tumors / cancer in Indonesia in 2017 is 1.4 per 1000 population, or around 347,000 people. The highest cancer in Indonesia in women is breast cancer and cervical cancer. Breast cancer is in the second position as the most common cancer affecting women in Indonesia after cervical cancer. The only most effective way that can be done for early detection of the possibility of this disease is to perform Breast Self-Examination (BSE). This study aims to determine the effect of health education with leafleat media on the knowledge of young women in early detection of breast cancer through breast self-examination at SMA N 8 Jambi City. The population in this study were young women at SMU N 8 Jambi City.The sampling using purposive sampling with 30 respondent. Data were analyzed using univariate and bivariate analysis with Paired Sample T Test. The results of the study concluded there was an effect of health education with leaflet media on the knowledge of young women in early detection of breast cancer through breast self-examination at SMA N 8 Jambi City (p value <0.005).